PkM Supervision of Foundation Work for the Construction of Mosque Campus-4 UMS - Sri Sunarjono; Budi Setiawan; Muh Ujianto (Prosiding University Research Colloquium, 2022)
he background of the campus 4 mosque UMS construction was because the capacity of the old mosque was very limited and to facilitate the participants of the Muhammadiyah congress. The construction is carried out on the self-managed basis. Construction work carried out with a very short period of time has a risk of controlling aspects, both quality, time, and cost. The purpose of the community service activity is to carry out supervision of the construction process for the foundation construction of the campus 4 UMS mosque. The method of community service activities uses a direct supervision approach in the field through quality, time, and cost control. Quality control is carried out with scheduled supervision of daily work and material quality testing. Time control is carried out using the basis of the work schedule plan and S curve. Meanwhile, cost control is carried out using the cost budget plan basis. The work supervision service activities resulted in the following: (i) the progress of the work was more controlled, (ii) the quality of the foundation materials was more standard and according to specifications, (iii) there was no delay in work, and (iv) the cash flow of project costs had to be anticipated by the contractor.